If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + 3(5x + -15) = 63 Reorder the terms: 3x + 3(-15 + 5x) = 63 3x + (-15 * 3 + 5x * 3) = 63 3x + (-45 + 15x) = 63 Reorder the terms: -45 + 3x + 15x = 63 Combine like terms: 3x + 15x = 18x -45 + 18x = 63 Solving -45 + 18x = 63 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '45' to each side of the equation. -45 + 45 + 18x = 63 + 45 Combine like terms: -45 + 45 = 0 0 + 18x = 63 + 45 18x = 63 + 45 Combine like terms: 63 + 45 = 108 18x = 108 Divide each side by '18'. x = 6 Simplifying x = 6
| 8+c=0 | | 8=c-12 | | x^2-14x+40=40 | | -0.23076923p=-2 | | -4(t-4)+9t=7t-6 | | (x-10)(x-4)=40 | | -3(1.2)(1.2)= | | 7y+5=9y | | 36.86=7g+3.54 | | -16-2n=n-4 | | 3(x+2)-7x=9(x-18)+9x-2 | | (23x+5)=22 | | -3+2x=1+x | | 30+10x=9x | | 6x+2(3x-7)=82 | | 1+3m=m+7 | | 4x+3=5(x-11) | | 52=10+c | | 4y+8x=13 | | -3+6m=15-3m | | 2=-17+c | | 7x+50=5x-14 | | 2a+7=5a+1 | | -0.231p=-2 | | 26-9x=10+7x | | -5x+15=-2x+3 | | 3a+4=6a-2 | | 2x^2+mx+3=x+1 | | f(x)=12+3x | | 12y+11=6y+41 | | 11y-6=93 | | 6(6-6n-3)+3=8n+29 |